Analisis Penggunaan Aplikasi Karejo Terhadap Efektivitas Kinerja Pegawai Di Dinas Perkebunan Provinsi Sumatera Utara - Siti Julia; Muhammad Ikhsan Harahap (Jurnal Manajemen Akuntansi (JUMSI), 2022)
The need for technology is increasingly felt in almost every aspect of life today. Information technology is a means and infrastructure (hardware, software, useware) systems and methods for obtaining, transmitting, processing, interpreting, storing, organizing, and using data meaningfully. The Plantation Service of North Sumatra Province has implemented the use of Information Technology (IT) to carry out all work activities. The information technology used is the Karejo application. Before using the karejo application service, the Plantation Service used another very simple application, the SKP application. Judging from its features, the Karejo application has more complete features. Internship activities are carried out from January 17 to February 17 2022. The results of the study are that the karejo application is used by two parties, namely by the direct supervisor and the civil servant concerned. The use of the karejo application for superiors is to control, evaluate employee performance, while for employees, the karejo application is used to report the work that is completed every day and is used to obtain TPP. The work done by employees can be completed on time, it's just that because the application used often has problems, causing a worker to not be able to do it effectively.